Stock and quantitative distribution of the Antarctic krill (Euphausia superba DANA) in the Antarctic Ocean south of Australia in January and February 1984 (abstract) - Inagake, Denzo; Matsuura, Noboru; Kurita, Yoshihiro (1986)
P(論文) departmental bulletin paper